Tujuan Pendidikan Dalam Islam - Sudarto Sudarto (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2020)
Education has a very urgent role in building a civilization. It can even be said that education is the main pillar in the effort to build a dignified civilization. Therefore, history records that no civilization has ever ruled the world but begins with science. However, Islamic education today has almost lost its prestige as a process that leads every child of Adam to become a whole human. Even though educational institutions have facilities, these institutions are still not quite successful in producing civilized human figures. This is because the vision and mission of education which leads to the formation of civilized humans are neglected in the objectives of educational institutions.In principle, the goals of Islamic education must be in line with the objectives of the Islamic message, in line with the objectives of Islamic law. Therefore, the aim of Islamic education must be universal and always be up to date with all ages, as always the teachings of Islam, so that the objectives of Islamic syari'at which want to realize rahmatan li al-alamin can truly be realized.The aim of education is essentially to produce human beings who behave in an Islamic manner, namely humans who believe and obey Allah as a source of absolute power that must be obeyed. Absolute obedience to God implies total surrender to Allah, making humans enslave themselves only to Him.